Reforming the European Scene - Joseph Ezra Bigio (Contemporary Economics)
An unbridled globalization based on a simple premise about earnings and profit may be detrimental to the livelihood of many thousands of individuals. The greed and utter selfishness that result from the adherence to this sort of business practice are the two things that generate more unemployment, misery and degradation than most other characteristics of the human species. These considerations present the challenge for Western societies and call for the implementation of other principles, standards and procedures, such as cooperation, cohesion, development objectives and social responsibility. In the first part of the paper this approach is tested in the case of the EU-US foreign exchange relationships. The second part of the paper raises more general and fundamental issues. While adhering to the Schumpeter-type innovation environment, it aims to introduce the social dimension ahead of the immediate competitiveness and, therefore, argues for the fundamental reform of the catechism of the capitalist manager. The EU, due to its advanced integration, is relatively well-equipped to move towards the new economic system.